THE MAIN PROBLEMS OF UZBEK AND FOREIGN METHODOLOGY ON TEACHING ENGLISH FOR SPECIAL PURPOSES - Y. X. Kushakov; G. S. Mustayeva (Sciental Journals Publishing, 2025)
In this article, the main problems of Uzbek and foreign countries' methodology on teaching ESP (English for special purposes) are revealed. The author highlights the key tendencies and problems in this sphere.
Keywords: ESP, Special Subjects. Various approaches, authentic material, teacher training.